Trends in US agricultural since 2000 and implications for the next twenty years - Glauber, Joseph W.; Smith, Vincent H. (Wiley, 2021)
Over the past 20 years, US agricultural policy has primarily served the interests of farm organisations whose members operate relatively large enterprises and the concerns of environmental and conservation lobbies about soil, water quality, wildlife quality and access to public lands. While maintaining the same underlying focus, over the past twenty years US agricultural policy has shifted from decoupled income support to price‐ and revenue‐based counter‐cyclical subsidy programmes, increased the coverage under a plethora of heavily subsidised agricultural insurance initiatives, and expanded the scope of conservation programmes. Further, between 2018 and 2020, there were unprecedented levels of additional spending through ad hoc measures to compensate producers for losses sustained as a result of the Trump administration’s trade wars and, more recently, losses attributed to the coronavirus pandemic. These levels of spending have been criticised as excessive relative to actual losses and likely caused the United States to violate its WTO domestic support commitments. However, US agricultural subsidy initiatives could soon involve more changes. The Biden administration wants to refocus some agricultural expenditure towards reducing greenhouse gas emissions and addressing concerns about the lack of financial support for minority groups, but probably not at the expense of funding for current programmes.